Model predictive control based energy management system literature assessment for RES integration - Tumeran, Nor Liza; Yusoff, Siti Hajar; Gunawan, Teddy Surya; Abu Hanifah, Mohd Shahrin; Zabidi, Suriza Ahmad; Pranggono, Bernardi; Mohd Yunus, Muhammad Sharir Fathullah; Mohd Sapihie, Siti Nadiah; Halbouni, Asmaa Hani (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Over the past few decades, the electric power industry evolved in response to growing concerns about climate change and the rising price of fossil fuels. The usage of renewable energy sources (RES) rose as a remedy for these problems. The increased penetration of RES in the existing generation system increased the need for an intelligent energy management system (EMS) so that the system can operate in any possible circumstances. Many sectors of society, including the education sector, are working to realize the importance of this sustainable energy system. This paper reviews the process of selecting an efficient control technique for continuous power flow from different RES to meet the load demand requirement using an enhanced model predictive control (MPC)-based EMS framework. This EMS is a software platform to provide fundamental support services and applications to deliver the functionality needed for the effective operation of electrical generation and transmission facilities to ensure adequate security of energy supply at minimum cost. The centralized EMS with technical objectives focusing on power quality and seamless power flow can be achieved through dynamically enhanced MPC.